Respuesta :

Step-by-step explanation:

The correct steps are:

2x²-2x-24=0

2(x²-x-12)=0

2(x-4)(x+3)=0

x=4 or x=-3

so what actually went wrong, is the final answer which is supposed to be x=4,-3 instead of x=-4,3

Answer:

x = 4, x = -3

Explanation:

⇒ 2x² - 2x -24 = 0

[tex]\sf takeout \ the \ common \ factor[/tex]

⇒ 2(x² - x - 12) = 0

[tex]\sf divide \ both \ sides \ by \ 2[/tex]

⇒ x² - x - 12 = 0

[tex]\sf breakdown[/tex]

⇒ x² - 4x + 3x - 12 = 0

[tex]\sf factor \ common \ terms[/tex]

⇒ x(x - 4) + 3(x - 4) = 0

[tex]\sf collect \ into \ groups[/tex]

⇒ (x - 4)(x + 3) = 0

[tex]\sf set \ to \ zero[/tex]

⇒ x = 4, x = -3